Highly thermally conductive blended polymer film based on electrospinning and its preparation method and application
Patent Information
- Application Number
- CN202310357804.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-06
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-04-06
AI Technical Summary
首先,在制备有机纳米纤维方面,用于静电纺丝的天然高分子品种还十分有限,对所得产品结构和性能的研究不够完善,最终产品的应用大都只处于实验阶段,尤其是这些产品的产业化生产还存在较大的问题
[0040](1)本发明经静电纺丝制备得到的聚偏氟乙烯-六氟乙烯在平面方向的导热系数可以达到2.18W m-1K-1,垂直面导热系数可以达到0.016W m-1K-1,面内导热系数为垂直方向导热系数的136倍,有很好的各向异性。
Smart Images

Figure CN116590848B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of thermally conductive composite materials, and specifically relates to a high thermal conductivity blended polymer film based on electrospinning, its preparation method and application. Background Technology
[0002] With the development of advanced electronics and high-frequency communication technologies, heat dissipation has become an increasingly critical factor restricting the lifespan and safe, stable operation of electronic devices. Therefore, the development of high thermal conductivity interface materials has become a major research hotspot in the field of polymer composites. Electrospinning offers advantages such as simple equipment, high production efficiency, and wide applicability of materials. Electrospinning can effectively improve the orientation of polymers, reduce phonon scattering, and increase the thermal conductivity of materials. Polyvinylidene fluoride (PVDF)-hexafluoropropylene copolymer (PPF-HCF) exhibits excellent thermodynamic properties and chemical stability, along with good releaseability. The horizontal and vertical thermal conductivity of PPF-HCF films formed by electrospinning show a significant difference, especially in the vertical direction where the thermal conductivity is only 0.047. To further improve its thermal conductivity, a liquid crystal polyester containing hydrogen bond donors was synthesized and added to the PPF-HCF copolymer to prepare a high thermal conductivity blend polymer.
[0003] The preparation of nanofiber materials through electrospinning has been one of the most important academic and technological activities in the field of materials science and technology worldwide in the past decade. Electrospinning, with its advantages of simple manufacturing equipment, low spinning cost, wide variety of spinnable materials, and controllable process, has become one of the main methods for effectively preparing nanofiber materials. Electrospinning technology has already prepared a rich variety of nanofibers, including organic, organic / inorganic composite, and inorganic nanofibers. However, the preparation of nanofibers using electrospinning technology still faces some challenges. First, in the preparation of organic nanofibers, the types of natural polymers used for electrospinning are still very limited, and research on the structure and properties of the resulting products is insufficient. The application of these products is mostly still in the experimental stage, especially the industrial production of these products, which faces significant problems. Second, the performance of electrospun organic / inorganic composite nanofibers is not only related to the structure of the nanoparticles, but also to the aggregation mode and synergistic properties of the nanoparticles, the structural properties of the polymer matrix, the interfacial structure and properties between the particles and the matrix, and the processing and composite technology. How to prepare high-performance, multifunctional composite nanofibers suitable for specific needs is the key to this research. In addition, research on electrospun inorganic nanofibers is basically in its initial stage. Inorganic nanofibers have potential applications in many fields such as high-temperature filtration, high-efficiency catalysis, biological tissue engineering, optoelectronic devices, and aerospace equipment. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings and deficiencies of the prior art and provide a high thermal conductivity blended polymer film based on electrospinning.
[0005] Another object of the present invention is to provide a method for preparing the above-mentioned high thermal conductivity blended polymer film based on electrospinning.
[0006] Another object of the present invention is to provide the application of the above-mentioned electrospun high thermal conductivity blended polymer film.
[0007] A high thermal conductivity blended polymer film based on electrospinning is prepared by electrospinning a liquid crystal polyester containing hydrogen bond donors and a polyvinylidene fluoride-hexafluoroethylene blend.
[0008] The mass fraction of the liquid crystal polyester containing hydrogen bond donors in the electrospun high thermal conductivity blended polymer film is 10-30%; preferably 20%.
[0009] The liquid crystal polyester containing hydrogen bond donors has the structural formula shown in Formula I:
[0010]
[0011] The electrospinning mentioned above refers to spinning using an electrospinning machine.
[0012] The above-mentioned method for preparing a high thermal conductivity blended polymer film based on electrospinning includes the following steps:
[0013] Liquid crystal polyester containing hydrogen bond donors and polyvinylidene fluoride-hexafluoroethylene are dissolved in a solvent, stirred, and added to an electrospinning machine for spinning. The resulting film is washed and dried to obtain a high thermal conductivity blend polymer film based on electrospinning.
[0014] The stirring conditions are 4 to 8 hours; preferably 6 hours.
[0015] The spinning conditions are as follows:
[0016] The solution is placed in a syringe, and spinning is performed at a speed of 0.2 to 1 mm / min under the conditions of a constant voltage of 8 to 12 kV, a receiving roller speed of 200 to 300 rpm, and a needle distance of 10 to 20 cm from the receiving roller.
[0017] The washing conditions described are washing with anhydrous ethanol.
[0018] The drying conditions were obtained by drying at 60°C for 4 hours.
[0019] The above-mentioned method for preparing liquid crystal polyester containing hydrogen bond donors includes the following steps:
[0020] (1) The haloalcohol, biphenyl hydrol and anhydrous potassium carbonate were refluxed under a protective atmosphere, cooled and then water was added, filtered, neutralized, washed with water and dried to obtain biphenyl dihexanol.
[0021] (2) After mixing biphenyl dihexanol and 5-hydroxyisophthalic acid, a catalyst was added and heated to react for polycondensation. Then, the reaction was continued while being filtered to obtain a liquid crystal polyester containing hydrogen bond donors.
[0022] The haloalcohol is at least one of 2-bromoethanol, 3-chloro-1-propanol, 4-chlorobutanol, or 6-chlorohexanol.
[0023] The molar ratio of the haloalcohol to biphenyl is 2 to 4:1; preferably 3:1.
[0024] The protective atmosphere is a nitrogen atmosphere.
[0025] The reflux reaction conditions are reflux for 20-30 hours; preferably reflux for 24 hours.
[0026] The cooling mentioned refers to cooling to room temperature.
[0027] The neutralization process involves adding hydrochloric acid to adjust the pH to 1.
[0028] The drying conditions are 70-90℃ for 20-30 hours; preferably 80℃ for 24 hours.
[0029] The molar ratio of biphenyl dihexanol to 5-hydroxyisophthalic acid is 1-2:1-2; preferably 1:1.
[0030] The catalyst is anhydrous zinc acetate and antimony trioxide.
[0031] The mass of the anhydrous zinc acetate is 0.1% to 0.3% of the total mass of the reaction system; preferably 0.2%.
[0032] The antimony trioxide comprises 0.2% to 0.4% of the total mass of the reaction system; preferably 0.3%.
[0033] The heating polycondensation reaction is carried out at 150-200°C for 2-4 hours; preferably at 180°C for 3 hours.
[0034] The vacuum filtration condition is a vacuum level of less than 30 Pa.
[0035] The conditions for continued heating reaction are to react at 150-200°C for 2-4 hours; preferably at 190°C for 3 hours.
[0036] The above-mentioned application of electrospun high thermal conductivity blended polymer films in the fabrication of electronic devices.
[0037] The above-mentioned electrospun high thermal conductivity blended polymer film is used as a heat dissipation material for electronic devices.
[0038] The objective of this invention is achieved through the following technical solution:
[0039] The present invention has the following advantages and effects compared with the prior art:
[0040] (1) The polyvinylidene fluoride-hexafluoroethylene prepared by electrospinning in this invention has a thermal conductivity of 2.18 W / m in the planar direction. -1 K -1 The thermal conductivity of the vertical plane can reach 0.016 W / m. -1 K -1 Its in-plane thermal conductivity is 136 times that in the vertical direction, and it has excellent anisotropy.
[0041] (2) The liquid crystal polyester synthesized in this invention has good thermal conductivity and contains hydrogen bond donors. It can form hydrogen bonds OH---F with polyvinylidene fluoride-hexafluoroethylene containing hydrogen bond acceptors. The thermal conductivity is further improved after the two polymers are blended and spun. Furthermore, composite films with different properties in the horizontal and vertical directions can be obtained by adjusting the ratio of the two polymers. When 20% of the liquid crystal polyester is added, its thermal conductivity in the planar direction can reach 5.25 W / m. -1 K -1 The thermal conductivity of the vertical plane can reach 0.127m. -1 K -1 Its in-plane thermal conductivity is 41 times that in the vertical direction. Attached Figure Description
[0042] Figure 1 These are SEM images of liquid crystal polyester and polymer films prepared in Examples 1-5.
[0043] Figure 2 These are the infrared spectra of the polyvinylidene fluoride-hexafluoroethylene-liquid crystal polyester blend films obtained in Examples 1 to 5.
[0044] Figure 3 This is a diagram of the thermal conductivity mechanism of the blended polymer. Detailed Implementation
[0045] The present invention will be further described in detail below with reference to the embodiments and accompanying drawings, but the embodiments of the present invention are not limited thereto.
[0046] Unless otherwise specified in the following implementation plan, the test conditions are generally as per standard test conditions or the test conditions recommended by the reagent company. Unless otherwise specified, all materials and reagents used are commercially available.
[0047] Example 1
[0048] This embodiment provides a method for preparing polyvinylidene fluoride-hexafluoroethylene membrane based on casting method.
[0049] 0.3g of polyvinylidene fluoride-hexafluoroethylene was dissolved in 6g of acetone solution and stirred thoroughly for 6 hours to form a homogeneous solution. The solution was placed in a polytetrafluoroethylene petri dish to evaporate the solvent and form a film. After the film was formed, it was peeled off and then placed in a vacuum oven at 60°C for 4 hours to obtain a polymer film.
[0050] The prepared polymer film was characterized, and the experimental results showed that the thermal diffusivity of the material in the horizontal direction was 2.168 mm. 2 s -1 The horizontal thermal conductivity is 1.735 W / m. -1 K -1 The vertical thermal diffusivity is 0.074 mm. 2 s -1 The thermal conductivity in the vertical direction is 0.059 W / m. -1 K -1 The in-plane thermal conductivity is 29 times that in the vertical direction.
[0051] Example 2
[0052] This embodiment provides a method for preparing polyvinylidene fluoride-hexafluoroethylene membrane based on electrospinning.
[0053] 1.2g of polyvinylidene fluoride-hexafluoroethylene was dissolved in 6g of NMP (N-methylpyrrolidone) solution and stirred thoroughly for 6h to form a homogeneous solution. The solution was placed in a 10ml syringe and spun at a speed of 0.5mm / min under the conditions of a constant voltage of 12KV, a receiving roller speed of 200rpm, and a needle distance of 10cm from the receiving roller. After spinning, the obtained film was washed in anhydrous ethanol solution and then placed in a vacuum oven at 60℃ for 4h to obtain a polyvinylidene fluoride-hexafluoroethylene membrane based on electrospinning.
[0054] The polymer film prepared by the above method has a horizontal thermal diffusivity of 3.449 mm. 2 s -1 The horizontal thermal conductivity is 2.18 W / m. -1 K -1 The vertical thermal diffusivity is 0.026 mm. 2 s -1 The thermal conductivity in the vertical direction is 0.016 W / m. -1 K -1 Its in-plane thermal conductivity is 132 times that in the perpendicular direction, exhibiting excellent anisotropy. Its SEM image is shown below. Figure 1 As shown, its surface is smooth, without bubbles or bumps.
[0055] Example 3
[0056] This embodiment provides a method for preparing highly thermally conductive blended polymers based on electrospinning.
[0057] (1) Place 40 ml of 6-chlorohexanol (halogenated alcohol), 18.6 g of biphenyl hydrochloride, and 124 g of anhydrous potassium carbonate in a 250 ml three-necked flask. Under nitrogen protection, reflux for 24 h. After cooling the reactants to room temperature, add deionized water and stir. Filter to remove the solvent. Add excess hydrochloric acid (pH 1) to react and remove excess potassium carbonate. Wash with water several times. Dry the resulting product in a vacuum oven at 80°C for 24 h to obtain biphenyl dihexanol. 3.54 g of biphenyl dihexanol and 1.8 g of... 5-Hydroxyisophthalic acid was polycondensed under the following conditions: 0.011 g of anhydrous zinc acetate and 0.016 g of antimony trioxide were added, and the reaction was carried out at 180°C for 3 hours. The temperature was then slowly increased to 190°C, and the system vacuum was reduced (below 30 Pa) by vacuum filtration to remove water and small molecules, thus promoting the polycondensation reaction in the forward direction. The reaction was continued at 190°C for another 3 hours, after which the reaction was stopped, and the product was collected to obtain a liquid crystal polyester containing hydrogen bond donors. Its structural formula is shown in Formula I, and the SEM image is shown below. Figure 1 As shown, the polymer has excellent crystallization properties and uniform grain size.
[0058]
[0059] (2) Dissolve 0.12g of the liquid crystal polyester prepared in Example 2 and 1.08g of polyvinylidene fluoride-hexafluoroethylene in 6g of NMP solution and stir thoroughly for 6h to form a homogeneous solution. Place the solution in a 10ml syringe and spin at a speed of 0.5mm / min under the conditions of a constant voltage of 12KV, a receiving roller speed of 200rpm, and a needle distance of 10cm from the receiving roller. After spinning, clean it in an ethanol solution and then treat it in a vacuum oven at 60℃ for 4h to obtain a high thermal conductivity blended polymer film based on electrospinning.
[0060] The polymer film prepared by the above method has a horizontal thermal diffusivity of 3.207 mm. 2 s -1 The horizontal thermal conductivity is 3.409 m. -1 K -1 The vertical thermal diffusivity is 0.071 mm. 2 s -1 The thermal conductivity in the vertical direction is 0.075 W / m. -1 K -1 The in-plane thermal conductivity is 45 times that in the vertical direction. SEM image as follows... Figure 1 As shown, the infrared spectrum is as follows Figure 2 As shown.
[0061] Example 4
[0062] This embodiment provides a method for preparing highly thermally conductive blended polymers based on electrospinning.
[0063] 0.24g of the liquid crystal polyester prepared in Example 3 and 0.96g of polyvinylidene fluoride-hexafluoroethylene were dissolved in 6g of NMP solution and stirred thoroughly for 6h to form a homogeneous solution. The solution was placed in a 10ml syringe and spun at a speed of 0.5mm / min under the conditions of a constant voltage of 12KV, a receiving roller speed of 200rpm, and a needle distance of 10cm from the receiving roller. After spinning, the solution was washed in an ethanol solution and then placed in a vacuum oven at 60℃ for 4h to obtain a high thermal conductivity blended polymer film based on electrospinning.
[0064] The polymer film prepared by the above method has a horizontal thermal diffusivity of 4.27 mm. 2 s -1 The horizontal thermal conductivity is 5.25 W / m. -1 K -1 The vertical thermal diffusivity is 0.103 mm. 2 s -1 The thermal conductivity in the vertical direction is 0.127 W / m. -1 K -1 The in-plane thermal conductivity is 41 times that in the vertical direction. SEM image as follows... Figure 1 As shown, the infrared spectrum is as follows Figure 2 As shown.
[0065] Example 5
[0066] This embodiment provides a method for preparing highly thermally conductive blended polymers based on electrospinning.
[0067] 0.36g of the liquid crystal polyester prepared in Example 3 and 0.84g of polyvinylidene fluoride-hexafluoroethylene were dissolved in 6g of NMP solution and stirred thoroughly for 6h to form a homogeneous solution. The solution was placed in a 10ml syringe and spun at a speed of 0.5mm / min under the conditions of a constant voltage of 12KV, a receiving roller speed of 200rpm, and a needle distance of 10cm from the receiving roller. After spinning, the solution was washed in an ethanol solution and then placed in a vacuum oven at 60℃ for 4h to obtain a high thermal conductivity blended polymer film based on electrospinning.
[0068] The polymer film prepared by the above method has a horizontal thermal diffusivity of 2.248 mm. 2 s -1 The horizontal thermal conductivity is 2.713 W / m. -1 K -1The vertical thermal diffusivity is 0.084 mm. 2 s -1 The thermal conductivity in the vertical direction is 0.101 W / m. -1 K -1 The in-plane thermal conductivity is 27 times that in the vertical direction. SEM image as follows... Figure 1 As shown, the infrared spectrum is as follows Figure 2 As shown, when the amount of liquid crystal polyester added is 30%, its spinnability deteriorates, resulting in a decrease in its thermal conductivity compared to Case 4.
[0069] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A high thermal conductivity blended polymer film based on electrospinning, characterized in that: The electrospun high thermal conductivity blend polymer film is prepared by electrospinning a liquid crystal polyester containing hydrogen bond donors and a polyvinylidene fluoride-hexafluoroethylene blend. The mass fraction of the liquid crystal polyester containing hydrogen bond donors in the electrospun high thermal conductivity blended polymer film is 10-30%. The electrospinning mentioned above refers to spinning using an electrospinning machine; The preparation method of the high thermal conductivity blended polymer film based on electrospinning includes the following steps: dissolving liquid crystal polyester containing hydrogen bond donors and polyvinylidene fluoride-hexafluoroethylene in a solvent, stirring, adding to an electrospinning machine for spinning, and washing and drying the resulting film to obtain the high thermal conductivity blended polymer film based on electrospinning. The liquid crystal polyester containing hydrogen bond donors has the following structural formula: ; The solution is placed in a syringe, and spinning is performed at a speed of 0.2-1 mm / min under the conditions of a constant voltage of 8-12 kV, a receiving roller speed of 200-300 rpm, and a needle distance of 10-20 cm from the receiving roller. The stirring conditions are 4–8 hours; The washing conditions described are washing with anhydrous ethanol; The drying conditions were obtained by drying at 60°C for 4 hours.
2. The application of the high thermal conductivity blended polymer film based on electrospinning as described in claim 1 in the preparation of electronic devices.
3. The application of the electrospun high thermal conductivity blended polymer film as described in claim 1 as a heat dissipation material for electronic devices.
Citation Information
Patent Citations
Heat radiation sheet and method for manufacturing same
CN104520100A
Electrode-separator integral segment for a lithium ion battery
US20130224602A1
